(untitled) (Olhar de Professor, 2012)
Contemporary times show the need for professionals from different sectors to take part in continuing formation processes, in particular teachers who should become lifelong learners. This demonstrates that every profession undergoes changes as a consequence of technological and scientific development. The teaching profession needs to follow the same logic, that is, to be aware of these changes and that this requires a systematic preparation through continuing education. Thus, this article highlights that continuing education is a consequence of society’s development and that it has been undertaken by a signifi cant percentage of teachers through distant education. This article discusses the implementation of the course Media in Education - Outreach Project - in the state of Rio Grande do Norte, carried out by the University of the State of Rio Grande do Norte (UERN) and by the Federal University of Rio Grande do Norte (UFRN). It is a distance education course developed in a virtual learning environment since 2005.